Power Doppler Ultrasound Assessment of A1 Pulley. A New Target of Inflammation in Psoriatic Arthritis? - Smerilli, Gianluca; Cipolletta, Edoardo; Di Carlo, Marco; Di Matteo, Andrea; Grassi, Walter; Filippucci, Emilio (Frontiers in Medicine, 2020)
Objective To determine the prevalence of grey scale and power Doppler (PD) ultrasound (US) features of A1 pulley inflammation in a cohort of psoriatic arthritis (PsA) patients compared with rheumatoid arthritis (RA) patients. Methods Sixty patients (30 with PsA and 30 with RA) were consecutively enrolled. The main clinimetric indexes were recorded and US assessment of A1 pulleys of fingers 2nd to 5th bilaterally was carried out. The presence of A1 pulley inflammation, defined as PD signal within a thickened pulley, was registered. Results A1 pulley inflammation was found in 15 out 240 fingers (6.3%) of 8 (26.7%) PsA patients and in 1 out of 240 fingers (0.4%) of 1 (3.3%) RA patient (p<0.01 and p=0.03 respectively). Seven out of 8 (88%) PsA patients with at least one inflamed A1 pulley had a moderate/high disease activity score. The regression linear analysis (R2=0.36, adjusted R2=0.31) showed that A1 pulley inflammation was correlated with disease activity in PsA (DAPSA) (β=0.43, p=0.03). Conclusion US A1 pulley inflammation appears to be relatively common at patient level in PsA, seems to be a characteristic feature of PsA compared to RA and correlates with DAPSA.